Pendekatan Penilaian Gedung Penting Yang Tidak Direncanakan Secara Patut: Studi Kasus: Tower Air Traffic Control Airnav Bandara Halu Oleo, Kendari - Masykur Kimsan (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
This study investigates the technical condition of the Air Traffic Control (ATC) tower at Halu Oleo Airport, Kendari, with a focus on its foundation and structure. The selection of this building is motivated by the critical need to ensure its safety and adequacy in earthquake-prone areas, particularly following the devastating Palu earthquake in 2018. This research encompasses a comprehensive scope of field testing, including visual surveys, soil testing using cone penetration tests and hand-boring, as well as non-destructive testing such as hammer tests, ultrasonic pulse velocity measurements, and rebars locators. The selection of these methods is tailored to the operational requirements of the building. Both field and laboratory analyses reveal significant shortcomings in the structure's compliance with required concrete strength standards for earthquake-resistant buildings. Additionally, deflections in the structure do not meet the necessary criteria for optimal performance during seismic events. Finite Element Method (FEM) analyses of the upper and foundation structures indicate that the foundation's load-bearing capacity is insufficient for demanded earthquake loads, while the upper structure's natural period exceeds standard requirements. For all seismic scenarios considered, the structure fails to meet criteria for deflection (serviceability) and strength, resulting in performance at the Immediate Occupancy – Life Safety level. This implies that while the structure is safe for use, it requires maintenance and repairs to achieve better performance levels. Recommendations for improvement include reinforcing the entire structure, from the foundation to the upper levels, with construction materials that meet earthquake standards, or constructing a new ATC building that adheres to current regulations. Consequently, this study offers an alternative approach for evaluating critical buildings in earthquake-prone areas.